PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK DALAM PEMBELAJARAN IPA FASE D - Asih, Chory; Prabowo, Chandra Adi; Ekowati, Evelyn (Universitas Muhammadiyah Surabaya, 2024)
21st century education emphasizes activities that actively involve students in their learning process. The result of observations that have been carried out show that the average indicator of student learning activeness in science learning is relatively low, which is 46,65%. The purpose of this research is to increase student activeness in science learning by implementing Project Based Learning (PjBL) model. This study is a classroom action research with 32 students of class VIIIE of SMPN 2 Jaten as a subjects. Data were obtained from observations, filling out questionnaires and documentation. The indicator of success in the research is increasing student learning activeness with a percentage of 80% or classified as active. The result of the research showed that student learning activeness increased from 65,28% (good) in cycle I to 85,38% (very good) in cycle II. The implementation of Project Based Learning (PjBL) model can increase student activity in phase D science learning by achieving a percentage of more than 80% in cycle II.